THE IMPACTS OF AUDIT COMMITTEE SIZE, INFORMATION ASYMMETRY, OPERATING CASH FLOW AND EXTERNAL AUDIT QUALITY ON EARNINGS MANAGEMENT OF MANUFACTURING COMPANIES IN INDONESIA - Ghina Atikah Azhar; Islahuddin Islahuddin (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2018)
This study was done to find out impacts of audit committee size, information asymmetry, operating cash flow and external audit quality on earnings management of manufacturing companies in Indonesia. Samples used were 35 of all manufacturing companies listed in the Indonesia Stock Exchange (IDX) in the period of 2011-2015. Audit committee size was determined by comparing the number of audit committee member in a company and the minimum requirement of audit committee member according to the regulation of Financial Services Authority (OJK). Information asymmetry, operating cash flow, and external audit quality were measured based on relative bid-ask spreads, total operating cash flow on the total company assets, and dummy variable of Big 4 and non-Big 4 accounting firms, respectively. The data obtained was analyzed by multiple linear regression analysis. The results indicated that independent variables simultaneously influence earnings management practice. Partially, operating cash flow and external audit quality affected earnings management whereas audit committee size and information asymmetry did not affect earnings management.